Analysis of the thermal-mechanical redox stability of Nb2TiO7 and Nb1.33Ti0.67O4 for SOFC application. Issue 7 (May 2018) - Thomas, T.; Qi, H.; Sabolsky, E.M.; Liu, X.; Zondlo, J.W.; Hart, R.
Abstract: Nb2 TiO7 and Nb1.33 Ti0.67 O4 was reported as a potential anode materials for Solid Oxide Fuel Cells (SOFCs) based on their stable reversible phase transformation and high electronic conductivity. A high-temperature redox dilatometry test was developed to monitor the linear expansion or contraction of Nb2 TiO7 and Nb1.33 Ti0.67 O4 synthesized through a solid-state route. XRD analysis confirmed the phase purity. It was found that Nb2 TiO7 contracts linearly up to 0.006% in a reducing atmosphere and this contraction is reversible in nature whereas Nb1.33 Ti0.67 O4 expands linearly up to 1.9% in an oxidizing atmosphere which is irreversible in nature at 800 °C. In addition, the electrical conductivity of the materials was analyzed in redox atmospheres. At 800 °C, Nb2 TiO7 showed an electrical conductivity of 1.35 S/cm in forming gas (5%H2 /95%N2 ) which increases to 85 S/cm upon the reduction of Nb2 TiO7 to Nb1.33 Ti0.67 O4 . This study emphasizes the importance of high-temperature redox dilatometry in the development of SOFC electrode materials.